Lateral resistance mechanism of a frame with deep beams and hanging mud walls in traditional Japanese residential houses. (1st October 2021) - Li, Zherui; Isoda, Hiroshi; Kitamori, Akihisa; Nakagawa, Takafumi; Araki, Yasuhiro; Que, Zeli
Highlights: Resistance mechanisms of structural elements in a traditional timber frame. Diagonal effect of the deep beam and interaction with beam-end joints. Influence of structural elements on the force distribution and bending of columns. Abstract: This paper presents a structural analysis of a frame with deep beams and hanging mud walls in traditional Japanese residential houses. Based on experimental investigations of a frame with deep beams and mud walls, as well as a series of substrate tests of a bare timber frame, mud wall, and mortise-tenon joints, it was shown that the resistance generated by the mortise-tenon joints, deep beams and hanging mud walls contributed to the lateral resistance mechanism of the entire structure. Furthermore, the interaction between the deep beam and beam-end joints in the frame was discussed, and it was confirmed that the diagonal effect of the deep beam was not only reflecting in the resistance provided by the deep beam, but also a positive influence on the maintaining the moment of the beam-end joints under large rotation. The superimposed resistance of all the components and the frame test results were found to be consistent. In addition, because the resistances of joints, deep beams and hanging mud walls were all transmitted by columns, the bending of the columns caused by the moment of joints as well as the shear force of the mud walls was considered.